Some Identities of 3-Prime Near-Rings Involving Jordan Ideals and Left Generalized Derivations - En-guady, Adel; Boua, Abdelkarim; Farhan, Enaam (Iraqi Journal of Science, 2021)
In the current paper, we study the structure of Jordan ideals of a 3-prime near-ring which satisfies some algebraic identities involving left generalized derivations and right centralizers. The limitations imposed in the hypothesis were justified by examples.